2002
DOI: 10.1086/342650
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Chemical Abundances in the Starburst Galaxy M82 and Hypernova Nucleosynthesis

Abstract: X-ray observations have shown that the chemical abundance in the starburst galaxy M82 is quite rich in Si and S compared to oxygen. Such an abundance pattern cannot be explained with any combination of conventional Type I and II supernova yields. In addition, the energy-to-heavy-element mass ratio of the observed hot plasma is much higher than the value resulting from normal supernovae. We calculate abundances for explosive nucleosynthesis in core-collapse hypernovae and show that the abundance pattern and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
2
20
2
Order By: Relevance
“…The less abundant O relative to Ne might imply that the progenitor is very massive, > 20 M (Umeda et al 2002). Umeda et al (2002) also insists that fast convective mixing in the progenitor star (Spruit 1992) creates more Ne and less O. Therefore, we concluded that the progenitor of DEM L241 was a very massive star.…”
Section: Diffuse Emissionmentioning
confidence: 76%
“…The less abundant O relative to Ne might imply that the progenitor is very massive, > 20 M (Umeda et al 2002). Umeda et al (2002) also insists that fast convective mixing in the progenitor star (Spruit 1992) creates more Ne and less O. Therefore, we concluded that the progenitor of DEM L241 was a very massive star.…”
Section: Diffuse Emissionmentioning
confidence: 76%
“…The O underabundance measured in the hot gas cannot be modeled with standard nucleosynthesis from the present generation of SNe II. Umeda et al (2002) suggested explosive nucleosynthesis in core-collapse hypernovae, but they predicted a large underabundance of Ne and Mg as well, which is not observed.…”
Section: Discussionmentioning
confidence: 95%
“…The first attempt to measure hot-gas-phase abundances in M82 has been made quite recently by Ptak et al (1997) and slightly revised by Umeda et al (2002), by analyzing ASCA X-ray (0.4-10.0 keV) spectra. Fe and O abundances as low as 1=20 solar and significantly higher (by a factor between 3 and 10) Si, S, Mg, and Ca ones have been obtained, also consistent with BeppoSAX results (Cappi et al 1999).…”
Section: Nebular Abundances Of M82 From the Literaturementioning
confidence: 99%
“…Then more O, C, Al are burned to produce a larger amount of burning products such as Si, S, and Ar. Therefore, hypernova nucleosynthesis is characterized by large abundance ratios of [Si,S/O], which can explain the abundance feature of M82 (110). The mixing region is enclosed with the dotted line at M mix (out).…”
Section: Energy Dependencementioning
confidence: 99%